Ostrom’s Design Principles as Steering Principles for Contractual Governance in “Hotbeds” - Taufik Haryanto; Josephine van Zeben; Kai Purnhagen (Forestry Faculty, Universitas Hasanuddin, 2022)
The sustainability of complex contractual governance in “hotbeds” depends on steering principles. Ostrom’s design principles provide an analytical framework for robust institutions that enable collective action and cooperative behaviour. The success of Ostrom’s design principles depends on the capacity of social entities to self-govern. This article explores the potential of Ostrom’s design principles as such steering principles for contractual governance in “hotbeds”. We find that the preconditions for successful contractual networks in “hotbeds” and the empirical situations underlying Ostrom’s design principles are comparable. Building on this comparability, we apply Ostrom’s design principles to contractual networks in “hotbeds” area theoretically, and then go on to demonstrate its applied value to three situations in West Papua, Indonesia.